Community-level responses and environmental fate of metformin in freshwater mesocosms - Blandford, Nicholas C.; Palace, Vince; Rodríguez-Gil, José Luis; Timlick, Lauren; Stanley, Madeline; Frank, Richard A.; Campbell, Sheena; Rudy, Martina; Marshall, Stephanie; Wynia, Abby; Clark, Thomas; Cunningham, Jessie; et al. (The Science of the total environment, 2024)
The type 2 diabetes drug metformin is among the most frequently prescribed, dispensed, and consumed pharmaceuticals worldwide; and its heavy use and poor breakdown means it is consequently detected in various wastewater treatment plant (WWTP) effluents and surface waters. The resulting environmental concentrations of metformin can have adverse impacts on aquatic ecosystems. An 8-week in-lake mesocosm experiment was conducted in a freshwater boreal lake at the IISD-Experimental Lakes Area (Ontario, Canada) to determine the environmental fate and effects of metformin. Mesocosms were assigned to nominal concentrations of 0, 5, or 50 μg L−1 metformin, in replicates of four. Biotic communities (i.e. microbial, phytoplankton, zooplankton, benthic macroinvertebrate) were assessed and complementary Lemna gibba and Daphnia magna bioassays were conducted in the laboratory. Metformin was extremely stable during the 8-week experiment, with mean measured concentrations of 0.00, 5.42, and 42.79 μg L−1 in mesocosm surface waters for the 0, 5, and 50 μg L−1 treatments, respectively. While trace amounts of metformin were detected in mesocosm sediments, the compound was primarily found in the water column. After over 1 year following metformin additions, the mean loss of metformin from surface water was 94.0 % and 91.0 % for the 5 and 50 μg L−1 treatment groups, respectively. No adverse effects of metformin treatment on the diversity, abundance, or biomass of microbial, phytoplankton, zooplankton, or benthic macroinvertebrate communities were found. Additionally, no survival or reproductive effects were observed in the 21-d Daphnia magna bioassays and no significant effects were observed in the 7-d Lemna gibba growth assays. No substantial metformin transformation to guanylurea was observed in mesocosm surface waters or sediments, likely due to a lack of bacterial degradation occurring within mesocosms relative to WWTPs. [Display omitted] •8-week in-lake mesocosms exposure assessing fate of metformin in aquatic system.•8-week in-lake mesocosms exposure assessing effects of metformin on lower trophic level biotic communities.•Metformin concentrations were relatively persistent across 8-week study.•Metformin was not broken down to guanylurea during study period.•No effects of biotic communities due to metformin exposure were observed.